Do Hedge Funds Value Sell-Side Analysts Differently? - Chen, Haosi (Chelsea); Puckett, Andy (Journal of Banking & Finance, 2023)
We provide novel insight into how hedge funds value sell-side analysts’ work product using analysts who are selected to Alpha magazine's All-star analyst research team. Alpha’s rankings are constructed using a methodology identical to its sister publication, Institutional Investor, except that only ballots from hedge funds are tallied. When compared to other institutional investors, hedge funds prefer analysts that provide more frequent earnings forecast and recommendation revisions. Consistent with hedge funds placing a greater value on negative private information, hedge funds favor analysts that provide less optimistic recommendations, issue more recommendation downgrades, and provide lower price targets. We also find that hedge funds exhibit a preference for analysts who systematically change their recommendations in the same direction as prior-quarter hedge fund portfolio activity. This activity is most consistent with analysts using their recommendations to curry favor with hedge fund managers.